The inter-temporal dimension to knowledge spillovers: any non-environmental reason to support clean innovation? - Christos Karydas (ETH Zurich, CER-ETH - Center of Economic Research, 2017)
How should governments best allocate their budget to support private research activities? The consensus in the literature is that sector-specific R&D support policies should be increasing in the degree of compatibility of sectoral innovation with the practices of the wider economy. Using a multi-sector endogenous growth model with in-house R&D and knowledge spillovers, it is shown, that accounting for the time it takes for an innovation to diffuse modifies this widely-accepted result. Wide applicability of green innovations alone does not justify higher research subsidies.
Keywords: O31; O33; Q54; Q55; Q58; H23; 330; Climate Policy; Industrial Policy; Innovation Spillovers; Technology Diffusion; Endogenous Growth; Klimapolitik; Industriepolitik; Innovation; Spillover-Effekt; Technologietransfer; Mehrsektoren-Modell; Endogenes Wachstumsmodell